Kadar Glukosa Darah Sewaktu pada Pasien PROLANIS Trimester I dan Trimester II - Mahardika Putri Sintya Dewi (Jaringan Laboratorium Medis, 2021)
Blood glucose level checks are generally carried out for people with Diabetes Mellitus (DM) to establish the diagnosis and monitor therapy and the emergence of complications, thus the progress of the disease can be monitored. Examination of blood glucose levels during or ad random can measure blood glucose levels without measuring the time of the last meal. The puskesmas has a Chronic Disease Control Program (PROLANIS) which aims to encourage participants with chronic illness to achieve optimal quality of life. PROLANIS is held every month by giving drugs and blood glucose checks when, in trimester I prolanis patients high sugar levels should be decreased in trimester II. Objective to find out the description of blood glucose levels when in trimester I and trimester prolanis patients in Banyumas Wangon II Health Center in 2019. Research Methods this study was an observational study with descriptive research criteria with a sample of all PROLANIS patients who examined blood glucose levels. Results the study subjects were 45 PROLANIS patients who were examined for blood glucose levels at the time. The results showed that 6 patients were male (41.31%) and 39 patients were female (58.69%) Conclusion this study shows the results of glucose levels in PROLANIS patients the highest male sex in trimester I was 901 and trimester II was 657, the highest blood glucose level in I trimester I was 1372 and trimester II 841. Compliance with this treatment remained a decline main measure in the process of changing blood glucose levels.